2019
DOI: 10.1111/1756-185x.13685
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcium score in female rheumatoid arthritis patients: Associations with apolipoproteins and disease biomarkers

Abstract: Aims and methods In rheumatoid arthritis (RA), cardiovascular (CV) comorbidities are a major cause of mortality. Coronary Calcium Score (CCS) assessed by computed tomography has been associated with RA prognosis. In this work, we aimed to assess CCS in female RA patients and determine CCS association with different clinical, laboratory and imaging disease parameters. Results We evaluated 60 female patients, with a mean age of 53.6 ± 10.4 years, a mean Disease Activity Score of 28 joints (DAS28) (4v) and Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Three of 23 studies that analyzed a possible association between PTH and arterial calcification found a positive association ( Tuersun et al, 2020 ; Wu et al, 2016b ; Billington et al, 2016 ) and twenty no association ( Alagoz et al, 2014 ; Arad et al, 1998 ; Billington et al, 2020 ; Grønhøj et al, 2016 ; Barbarash et al, 2016 ; Cancela et al, 2012 ; Davaine et al, 2016 ; Diederichsen et al, 2017 ; Golovkin et al, 2016 ; Masai et al, 2013 ; Pirro et al, 2013 ; Torii et al, 2016 ; Razavi et al, 2021 ; Martín-Reys et al, 2016 ; Cm et al, 2009 ; Bellasi et al, 2013 ; Soares et al, 2015 ; Bernandes et al, 2019 ; Kim et al, 2012 ; Watson et al, 1997 ). In the included articles there were two studies that were longitudinal ( Alagoz et al, 2014 ; Diederichsen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three of 23 studies that analyzed a possible association between PTH and arterial calcification found a positive association ( Tuersun et al, 2020 ; Wu et al, 2016b ; Billington et al, 2016 ) and twenty no association ( Alagoz et al, 2014 ; Arad et al, 1998 ; Billington et al, 2020 ; Grønhøj et al, 2016 ; Barbarash et al, 2016 ; Cancela et al, 2012 ; Davaine et al, 2016 ; Diederichsen et al, 2017 ; Golovkin et al, 2016 ; Masai et al, 2013 ; Pirro et al, 2013 ; Torii et al, 2016 ; Razavi et al, 2021 ; Martín-Reys et al, 2016 ; Cm et al, 2009 ; Bellasi et al, 2013 ; Soares et al, 2015 ; Bernandes et al, 2019 ; Kim et al, 2012 ; Watson et al, 1997 ). In the included articles there were two studies that were longitudinal ( Alagoz et al, 2014 ; Diederichsen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 30 studies performed analyses on a possible association between 25-hydroxyvitamin D (25(OH)D) and arterial calcifications ( Billington et al, 2020 ; Grønhøj et al, 2016 ; Tuersun et al, 2020 ; Zagura et al, 2011 ; Davaine et al, 2016 ; Liu et al, 2019 ; Pirro et al, 2013 ; Awan et al, 2010 ; Razavi et al, 2021 ; Bernandes et al, 2019 ; Kim et al, 2012 ; de Boer et al, 2009 ; Cheru et al, 2019 ; Doherty et al, 1997 ; El Mokadem et al, 2021 ; Eyyüpkoca et al, 2021 ; Ho et al, 2015 ; Kiani et al, 2013 ; Lai et al, 2013 ; Lee et al, 2016 ; Lim et al, 2012 ; Michos et al, 2009 ; Moradi and Foroutanfar, 2017 ; Nikolova et al, 2021 ; Rodrigues et al, 2021 ; Sajjadieh et al, 2020 ; Satilmis et al, 2015 ; Shikuma et al, 2012 ; Sung et al, 2016 ; Janus et al, 2021 ). Of these, ten studies found a negative association between 25(OH)D and arterial calcification ( Zagura et al, 2011 ; Pirro et al, 2013 ; de Boer et al, 2009 ; Doherty et al, 1997 ; El Mokadem et al, 2021 ; Eyyüpkoca et al, 2021 ; Lai et al, 2013 ; Lee et al, 2016 ; Moradi and Foroutanfar, 2017 ; Nikolova et al, 2021 ), two a positive association ( Zagura et al, 2011 ; Sung et al, 2016 ) and nineteen no significant association ( Billington et al, 2020 ; Grønhøj et al, 2016 ; Tuersun et al, 2020 ; Davaine et al, 2016 ; Liu et al, 2019 ; Awan et al, 2010 ; Razavi et al, 2021 ; …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Additionally, the use of CAC in patients with risk-enhancing factors such as RA is useful in helping to reclassify risk and enhance decision-making regarding statin therapy. 27,28 Age is a major driver of 10-year risk estimation for CVD events. Many patients with RA are diagnosed at a younger age with lower cholesterol levels and therefore will likely score low on risk scoring systems.…”
Section: Cvd Screening Toolsmentioning
confidence: 99%